THE STUDY OF CONSUMER TRUST IN ONLINE SHORT-TERM HOMESTAY RENTAL IN THE CONTEXT OF SHARING ECONOMY - Zhu, Jing (Chinese Journal of Social Science and Management, 2023)
In recent years, the continuous development of rural tourism and sharing economy in China has caused homestay, as an emerging sharing economy, to experience explosive growth. However, a series of contradictions and problems between buyers and sellers have also emerged. The characteristics of the sharing mode make the problem of interpersonal trust become one of the key factors that limit its development. The establishment of trust between sharing subjects is the core and foundation for the healthy development of consumer behavior as well as the tourism-sharing economy. Based on the trust theory, the trust transfer theory and consumer behavior based on the rational behavior theory, this paper attempted to analyze the inﬂuence of online short-term rent trust on consumer behavior under the background of the sharing economy. In this model, the regulating eﬀect of folk customs was added to further explore the formation mechanism of online short-rent consumption behavior at homestay facilities under the background of the sharing economy. This study focused on the online short-rent consumers of homestay accommodations as the research sample and carried out research using the background of the sharing economy in China.